FAKTOR- FAKTOR YANG BERHUBUNGAN DENGAN KINERJA PETUGAS REKAM MEDIS SILOAM SRIWIJAYA HOSPITAL PALEMBANG TAHUN 2016 - Pestaria Saragih (Elisabeth Health Jurnal, 2019)
The hospital consists of pillars of owners, pillars of health professionals and management pillars. The pillar of health professional staff consists of various important elements, one of which is medical record staff. Hospitals do division of tasks in each department, according to their duties and functions. The results of implementing these functions are called performance. Organizational characteristics that affect individual performance consist of resources, leadership, rewards, organizational structure and work design. Goals: This study aims to analyzed the factors related to the performance of Siloam Sriwijaya Hospital Palembang medical record staff in 2016. Method: This type of research was quantitative, analytical survey method with cross sectional approach. When the study was conducted in August 2016 in the medical record of Siloam Sriwijaya Hospital Palembang. The population was all 33 medical records. The sample was a total population of 33 people. Techniques for collecting data with documentation and questionnaires. Measurements on variables of motivation, age, duration of work, education and leadership on the performance of medical record staff using a Likert scale. Bivariate statistical analyzed with Chi Square and multivariate test with Logistic Regression. Results: The results of the study was of only 2 that were significantly related to performance, namely motivation and leadership. Motivational variables after multivariate analysis and after selection with other independent variables still hav e a statistically significant relationship, where: OR: 5,012 (95% CI: 1,513 -16,601) p = 0,008 gives an interpretation that low motivation has a tendency to 5,012 times for have low performance too. Conclusion: Motivational variables had a significant relationship so that low motivation has a tendency to have low performance too. Director of Siloam Sriwijaya Hospital Palembang is always necessary to motivate officers and be rewarded when achieving achievement in the goals of the organization with staff under the leadership's coordination.